Pengaruh Stres Kerja, Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Amak Firdaus Utomo Kota Probolinggo - Basori, Saipullah; Yatiningrum, Agung; Widayanto, Mutinda Teguh (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at PT Amak Firdaus Utomo, Probolinggo City with the aim of this research being to examine the influence of work stress, workload and work environment on employee performance at PT. Amak Firdaus Utomo, Probolinggo City. The population in this study were employees of PT Amak Firdaus Utomo, Probolinggo City, totaling 393 employees. The sample in this study uses the technique used in this research is the simple random sampling technique. According to Dewi&Pertiwi in (Devi et al, 2023) "If there are less than 100 subjects, it is better to take all of them, and if there are more than 100 subjects then the sample is taken between 10% - 15% - or 20% - 25% or more. The sample used in this research was 59 employees of PT Amak Firdaus Utomo, Probolinggo City. Analysis was carried out using validity tests, reliability tests, classical assumption tests, multiple linear tests, coefficient of determination, and hypothesis tests. The results of this research show that: (1). The work stress variable has an influence on employee performance, (2). Workload variables have an influence on employee performance, (3) work environment variables have an influence on employee performance.